A high temperature constitutive equation for AA 2014 PM alloy and its application to isothermal forging. (4th August 2014) - Forcellese, A.
The flow behaviour of AA 2014 PM aluminium alloy was studied at temperatures from 250 to 500°C, with strain rates of 5 x 10 −3, 5 x 10 −2 and 5 x 10 −1 s −1 . At given temperatures and strain rates, flow curves exhibit a peak followed by flow softening up to fracture. Moreover, at constant strain, flow stress increases with increasing strain rate and decreasing temperature. An equation relating the hyperbolic sine of flow stress to the temperature modified strain rate was used to describe the flow behaviour versus the working parameters. The dependence of constitutive parameters on strain was analysed at strain values that are typical of the practical operations and at temperatures from 350 to 450°C since in this range the hot formability is the highest. A very good agreement was found between predicted and experimental flow stresses in all the strain range investigated. Finally, the application of the constitutive equation in predicting the forming loads and the flow behaviour in an isothermal forging process by means of a finite element code was analysed.